Construction of an alkaline phosphatase-liposome system: a tool for biomineralization study - Camolezi, F. L.; Daghastanli, KRP; Magalhaes, P. P.; Pizauro, J. M.; Ciancaglini, P. (Elsevier B.V., 2002)
Alkaline phosphatase is required for the mineralization of bone and cartilage. This enzyme is localized in the matrix vesicle, which plays a role key in calcifying cartilage. In this paper. we standardize a method for construction an alkaline phosphatase liposome system to mimic matrix vesicles and examine a some kinetic behavior of the incorporated enzyme. Polidocanol-solubilized alkaline phosphatase, free of detergent, was incorporated into liposomes constituted from dimyristoylphosphatidylcholine (DMPC), dilaurilphosphatidylcholine (DLPC) or dipalmitoylphosphatidylcholine (DPPC). This process was time-dependent and >95% of the enzyme was incorporated into the liposome after 4 h of incubation at 25 degreesC. Although, incorporation was more rapid when vesicles constituted from DPPC were used, the incorporation was more efficient using vesicles constituted from DMPC. The 395 nm diameter of the alkaline phosphatase-liposome system was relatively homogeneous and more stable when stored at 4 degreesC.Alkaline phosphatase was completely released from liposome system only using purified phosphatidylinositol-specific phospholipase C (PIPLC). These experiments confirm that the interaction between alkaline phosphatase and lipid bilayer of liposome is via GPI anchor of the enzyme, alone. An important point shown is that an enzyme bound to liposome does not lose the ability to hydrolyze ATP, pyrophosphate and p-nitrophenyl phosphate (PNPP), but a liposome environment affects its kinetic properties, specifically for pyrophosphate.The standardization of such system allows the study of the effect of phospholipids and the enzyme in in vitro and in vivo mineralization, since it reproduces many essential features of the matrix vesicle. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: Alkaline phosphatase; Osseous plate; glycosyl phosphatidylinositol anchor (GPI) liposome; endochondral ossification